Prognostic Stratification Based on a Novel Nomogram for Solitary Large Hepatocellular Carcinoma After Curative Resection - Zhuang, Hongkai; Zhou, Zixuan; Ma, Zuyi; Huang, Shanzhou; Gong, Yuanfeng; Zhang, Zedan; Hou, Baohua; Yu, Weixuan; Zhang, Chuanzhao (Frontiers in Oncology, 2020)
Solitary large HCC (SLHCC) is a specific subtype of HCC with unique characteristic. It is of great interest to assess and stratify the prognosis of SLHCC after curative resection. In this study, we tried to construct a prognostic nomogram for SLHCC following curative resection through a retrospective analysis in 202 cases of SLHCC. Seven prognostic factors were identified and integrated to establish a novel prognostic nomogram, which are tumor size, microvascular invasion, tumor differentiation, Ki67, AFP, CA125, and HBsAg status. The Harrell’s concordance indexes (C-indexes) of the nomogram for overall survival (OS) in the training, validation, and whole sets were 0.752, 0.703, and 0.733, respectively. Furthermore, the area under the curve (AUC) of the receiver operating characteristic (ROC) curve of the nomogram for predicting 1-, 3-, and 5-year OS indicated the nomogram had an optimal discrimination of prognostic prediction for SLHCC. The total score of each patients were calculated based on the nomogram and patients were divided into three subgroups: low-risk group (a total score≦107), medium-risk group (107＜a total score≦125), and high-risk group (a total score＞125). The 1-, 3-, and 5-year OS rates of the low-risk group, medium-risk group, and high-risk group in the whole set were 89.3% vs 70.1% vs. 33.3%, 76.6% vs 37.8% vs. 14.5%, and 69.8% vs 25.1% vs. 12.5%, respectively (P < 0.001). Similar results were shown in terms of RFS. By analyzing 101 cases of recurrent tumors, transarterial chemoembolization (TACE) plus radiofrequency ablation (RFA)/surgery was found to prolong patients’ survival when compared to TACE alone in the low-risk group, but not in the medium/high-risk group. In conclusion, our prognostic nomogram successfully stratifies prognosis for SLHCC after curative resection, which deserves further study in future clinical practice.